Prevalence of ultrasound-determined cystic endometrial hyperplasia and the relationship with age in dogs - Moxon, Rachel; Whiteside, Helen; England, Gary C.W. (Elsevier, 2016)
To investigate the potential relationship between age and diagnosis of cystic endometrial hyperplasia (CEH) in the bitches, 348 ultrasound examinations from 240 bitches (Labradors, Golden Retrievers, German Shepherds, Flat Coated Retrievers, or crosses of those breeds aged between 1.6 and 7.2 years at examination) were examined. A subpopulation of 32 bitches that had completed their breeding careers at 6 years or more of age was also identified. Of all, 18.3% of the bitches were diagnosed with CEH; these cases were newly diagnosed when bitches were between 2.5 years and 7.3 years of age. The proportion of ultrasound examinations in which CEH was identified increased from 6.8% of examinations on 2-year-old breeding bitches to 60.0% of examinations on 6-year-old bitches. Logistic regression identified a positive correlation between mean age at the examination and presence of CEH (χ2 = 30.74, degrees of freedom = 1, P < 0.001). For 32 bitches that had completed their breeding career, the prevalence of CEH was 56.3%, age at the diagnosis ranged from 3.8 to 7.3 years, and the proportion of bitches affected with CEH increased from 6.3% at 3 years of age to 56.3% at 7 years of age. These data support the contention that the prevalence of CEH increases with age.